INFLUENCE OF TERMS AND RATES OF BIOSTIMULANTS APPLICATION ON THE DYNAMICS OF LEAF DEVELOPMENT IN MUNG BEAN VARIETIES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article studies the effect of the timing and rates of the use of biostimulants (Phytobiosol, Gumi-20, Avangard Start) on the development of leaves in mung bean varieties "Durdona" and "Marjon". Experimental work was carried out in 2022–2024 at two planting densities (200 and 300 thousand plants/ha). According to the results of the experiment, the largest number of leaves (16.5 pcs.) was recorded in the variety "Durdona" when treated with the biostimulant Avangard Start at a planting density of 200 thousand plants/ha the number of leaves. The positive effect of biostimulants activated the growth of leaves, which confirms their importance in the development of effective agricultural technology.